Study on Groundwater Quality Using Geographic Information System (GIS), Case Study: Ardabil, Iran - Ghasemlounia, Redvan; Sedaghat Herfeh, Nasim (Salehan Institute of Higher Education, 2017)
This study involves the analysis of water resources pollution data using Geographic Information System (GIS), which is a subset of the purposes such as: study on the status (situaion) of the aquifer, the natural and man-made effects on aquifer quality, evaluation and investigation of quality monitoring results of Ardabil aquifer, study on quality limitations by comparing the results of analysis of wet and dry seasons from water resources with selected standards. Therefore, samples were collected from76 wells, in this region, for the purpose of the aquifer water quality assessment, identification of changing process of pollution and statistical analysis of quality parameters included NTU, TDS, Nitrates and Chloride. Afterwards, maps for each parameter were produced in the geographic information system (GIS) using scientific methods. Thereupon, situation and condition of water quality was measured by quality mapping index of NSFWQ and was applied for whole the basin. This maps and database, which were created by the software, provide and offer an obvious view of what happened in the study area. As a result, it could be applied for a better management of these water resources and planning to prevent further pollution, by relevant organizations.